Nitric Oxide, Protein Oxidation and Total Antioxidant Levels in Serum of Dogs Naturally Infected by Ehrlichia canis, Leishmania infantum and Babesia vogeli - Baldissera, Matheus Dellamea; Marques de Sousa, Keyla Carstens [UNESP]; Andre, Marcos Rogerio [UNESP]; Guarda, Naiara dos Santos; Moresco, Rafael Noal; Herrera, Heitor Miraglia; Machado, Rosangela Zacarias [UNESP]; Santos Jaques, Jeandre Augusto dos; Tinucci-Costa, Mirela [UNESP]; Da Silva, Aleksandro Schafer (Univ Fed Rio Grande Do Sul, 2015)
Background: Ehrlichia canis and Babesia vogeli comprise a group of globally distributed pathogens transmitted by ticks. Leishmania infantum is transmitted by Lutzomyia longipalpis, etiological agent of leishmaniasis. The pathogens affect the animals; and can also affect the human. An imbalance between oxidants and antioxidants compounds causes an increase in free radicals, and other reactive oxygen species (ROS) has play an important role in tissue damage in a variety of pathological processes, as parasitic disease. The objective of this study was to evaluate the nitric oxide levels, protein oxidation and total antioxidant status in serum of dogs infected by L. infantum, E. canis and B. vogeli. Materials, Methods & Results: Blood samples from dogs originating from the city of Campo Grande, Mato Grosso do Sul state, Brazil were collected to research hemoparasites by polymerase chain reaction (PCR) using specific primers for each parasite. Serum samples obtained from 54 dogs with single and co-infection were used this study: L. infantum (n = 19), E. canis (n = 8), B. vogeli (n = 5), L. infantum and E. canis (n = 12), L. infantum and B. vogeli (n = 4), and E. canis and B. vogeli (n = 6), as well as 17 normal controls (uninfected). Samples were stored at -80 degrees C for further evaluation of NOx, AOPP, and FRAP levels using Cobas Mira automated analyzer, and results were expressed as mu mol/L. NOx, AOPP and FRAP levels were increased (P < 0.01) in dogs infected by parasites when compared to uninfected animals. Levels of NO. and AOPP in dogs naturally infected by Babesia vogeli and Ehrlichia canis, respectively, did not differ from the control group (uninfected). The higher NOx levels were observed in the serum of dogs with co-infection by L. infantum and E. canis, and L. infantum and B. vogeli (P < 0.01). Altogether, our results indicate that dogs naturally infected by L. infantum, E. canis and B. vogeli developed a state of redox imbalance. Discussion: Oxidative stress in dogs infected by L. infantum, Ehrlichia canis, and B. vogeli, single or co-infected were verified this study. As a result, naturally infected dogs sampled in the present study showed augmented levels of ROS, as well as in serum samples of dogs infected by Babesia gibsoni, Leishmania spp., Hepatozoon canis, and Trypanosoma evansi. Nitric oxide increased (detected by high NOx levels) can be a marker of oxidative stress, as well as an important mediator of inflammatory response. In experimental conditions, an increased level of NOx in dogs infected with E. canis was observed, and researchers say this increase was directly related to the pathogenesis of the disease. The imbalance of oxidants and antioxidants is present in various animal species in many pathological situations including parasitic diseases, as in dogs infected by hemoparasites showed increased oxidative markers (NO. and AOPP) associated with increased antioxidant levels (FRAP), which features a status of oxidative stress. The increase of FRAP is interpreted as the elevation of total antioxidant levels, i.e. enzymatic and non-enzymatic. The increased antioxidant is good to the host, it has the function of neutralizing the oxidizing or reducing that when high levels are toxic to cells and tissues. Therefore, we suggest that the infections caused by these hemoparasites cause oxidative stress and this process may participate in disease pathology.
Keywords: babesiosis; ehrlichiosis; leishmaniasis; canine; oxidative stress